How to do your research project : a guide for students in education and applied social sciences - Thomas, Gary, 1950- (SAGE; London, 2013)
Direct, informative and accessible, this edition of Gary Thomas's book is essential reading for anyone doing a research project. Packed full of relevant advice and real world examples it guides you through the complete research process.
Your introduction : starting points -- Preparing : project management, ethics and getting clearance -- The literature review -- Decide on your question -- again -- Methodology, part 1 : deciding on an approach -- Methodology, part 2 : the design frame -- The right tools for the job : data gathering -- How to analyse the information you gather -- Concluding and writing up.
Includes bibliographical references and index.
Keywords: Education -- Research -- Methodology; Social sciences -- Research; Social sciences -- Research -- Methodology; Society; Education -- Research -- Methodology..; Social sciences -- Research..; Social sciences -- Research -- Methodology..; Society